Metamodel-based formalization of DEVS atomic models. (May 2023) - Blas, María Julia; Gonnet, Silvio
The Discrete-Event System Specification (DEVS) formalism is a modeling formalism based on systems theory that provides a general methodology for hierarchical construction of reusable models in a modular way. When concrete DEVS models are developed using programming languages, it is difficult to ensure they conform to their formal model. Hence, building an implementation of formal models in a way that ensures DEVS formalism correctness is not easy. In this paper, we improve the interplay of abstraction (i.e., formal specification) and concreteness (i.e., programming code implementation) in advancing the theory and practice of DEVS using a specific-designed metamodel. The main contribution is a novel conceptualization of classic DEVS with ports founded on existing approaches but that also includes new improved elements related to the definition of atomic models. That is, our metamodel includes all the concepts and relationships needed to define the formal specification of DEVS atomic models. This allows us to define instances of our conceptualization that comply with the DEVS formal specification. To instantiate our metamodel, we propose a computer-aided environment that has been developed using the Eclipse Modeling Project. As an example, we show how our metamodel can be used to define the classic "switch" model. As a conclusion, we discuss how the final metamodel can be used to support interoperability with DEVS simulation tools.